The compassionate mind : a new approach to life's challenges - Gilbert, Paul, 1951 June 20- (2010)
In this work, Paul Gilbert explores how our minds have developed to survive in dangerous and threatening environments by becoming sensitive and quick to react to perceived threats.
Originally published: 2009.
Includes bibliographical references and index.
Keywords: Compassion; Emotional intelligence; Well-being.; Self-help techniques; Psychology